2010
DOI: 10.1017/s0033822200045628
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Origin of Cremated Bone Apatite Carbon

Abstract: Bones that have undergone burning at high temperatures (i.e. cremation) no longer contain organic carbon. Lanting et al. (2001) proposed that some of the original structural carbonate, formed during bioapatite formation, survives. This view is based on paired radiocarbon dating of cremated bone apatite and contemporary charcoal. However, stable carbon isotope composition of carbonate in cremated bones is consistently light compared to the untreated material and is closer to the δ13C values seen in C3 plant mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
97
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 28 publications
9
97
0
3
Order By: Relevance
“…In calcined bones with ô 13 C values lower than -25%o, we show that 67 ± 3% to 91 ± 8% of the carbon present in bone carbonate come from C0 2 present in the atmosphere of combustion. This finding confirms earlier results based on laboratory experiments (Hüls et al 2010;Van Strydonck et al 2010). …”
Section: Carbon Exchange During Calcinationsupporting
confidence: 93%
See 3 more Smart Citations
“…In calcined bones with ô 13 C values lower than -25%o, we show that 67 ± 3% to 91 ± 8% of the carbon present in bone carbonate come from C0 2 present in the atmosphere of combustion. This finding confirms earlier results based on laboratory experiments (Hüls et al 2010;Van Strydonck et al 2010). …”
Section: Carbon Exchange During Calcinationsupporting
confidence: 93%
“…The comparison of the ô 13 C of the charred (black) and calcined (white) portions of the same bone indicates that these modifications are highest in the calcined portions (Olsen et al 2008). Recently, laboratory experiments performed on modern bones showed that bone 14 C activity was also modified during calcination (Hüls et al 2010;Van Strydonck et al 2010). Calcination of modern bone in the presence of old C0 2 resulted in a decrease in bone 14 C activity, which paralleled the decrease in 5 13 C values (Hüls et al 2010).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, bicarbonate exchange reactions with fossil bones commonly result in 14 C ages too young (Tamers and Pearson 1965;Hassan et al 1977;Hedges and Millard 1995;Surovell 2000), which, if true, pushes the start of period III further back in time. Recent results suggest that the carbon isotope composition of cremated bones probably reflects the CO 2 of the burning atmosphere (Hüls et al 2010;van Strydonck et al 2010). This indicates the possibility of cremated bone samples being affected in a similar fashion as charcoal samples by the "old wood" effect.…”
Section: Resultsmentioning
confidence: 99%